Multi-actor scenarios to build capacity for food systems governance at the sub-continental level - Vervoort, Joost M.; Ingram, J.; Ericksen, Polly J.; Chaudhury, M.; Förch, Wiebke; Thornton, Philip K.; Kristjanson, Patricia M. (2012)
Global pressures on food security such as climate change, rising food prices and rising populations demand collaborative action from actors governing food systems across all levels and scales. This paper describes concerted efforts in East Africa, West Africa and South Asia to build capacity for food system governance at the regional (sub-continental) level where key environmental and socio-economic change processes play out. The Climate Change, Agriculture and Food Security (CCAFS) program is a partnership between the global agricultural development institutes (CGIAR) and the global environmental change community (ESSP). CCAFS uses multi-actor scenarios development processes to bring together regional actors from civil society, NGOs, the private sector, national governments, regional governance institutions, media and research. Together, these actors use exploratory scenarios of the future to consider radically different, plausible socio-economic development pathways for their regions. These alternate futures explore different roles for state and nonstate actors and interactions between national and regional governance efforts in terms of food security, environmental management and livelihoods. The scenarios also explore the consequences of reactive and proactive modes of governance and the focus on short term priorities versus long term priorities. This paper reports on how developing these socioeconomic scenarios creates collaborative multi-sector networks in East and West Africa and South Asia that together focus on key regional uncertainties. Furthermore, we discuss the subsequent use of the scenarios to test strategies, policies and technologies with state and non-state actors to build capacity for regional governance.